More nature in the city. (6th November 2020) - Capotorti, G; Bonacquisti, S; Abis, L; Aloisi, I; Attorre, F; Bacaro, G; Balletto, G; Banfi, E; Barni, E; Bartoli, F; Bazzato, E; Beccaccioli, M; et al.
Abstract: According to projects and practices that the Italian botanists and ecologists are carrying out for bringing " more nature in the city ", new insights for a factual integration between ecological perspectives and more consolidated aesthetic and agronomic approaches to the sustainable planning and management of urban green areas are provided.